Habitat suitability, core habitats and diversity hotspots for the conservation of the mustelid species in Iran - Kamran Almasieh (Global Ecology and Conservation, 2022)
The process of habitat loss and fragmentation is inevitable with increasing human activities, necessitating conservation for the areas with the highest priorities (i.e., biodiversity hotspots). This study aimed to predict the core habitats of the eight mustelid species (family: Mustelidae) in Iran and detect mustelid diversity hotspots based on the highest species richness of these species to compare them with available conservation areas (CAs). Accordingly, habitat suitability modeling was carried out for each mustelid species through an ensemble approach, and species richness and mustelid diversity hotspots were determined by overlaying the predicted core habitats. The results revealed that the highest richness of the mustelid species was six species for the overlaid map of the modeled core habitats. The main mustelid diversity hotspots were along the Alborz Mountains and the Hyrcanian forest of northern Iran. There were some other hotspots along the Zagros Mountains in western Iran. CAs protected less than half of mustelid diversity hotspots, which means that wildlife managers should take into consideration the conservation action plan for the mustelid species in Iran. Besides, it is necessary to expand available CAs or establish new-targeted CAs according to mustelid diversity hotspots.